THE PREDICTIVE POWER OF EARNINGS AND CASH FLOWS (TESTING AT THE EVERY STAGE OF COMPANY’S LIFE CYCLE) - Dyah Ayu Kusuma Wardhani; Luciana Spica Almilia (Universitas Hayam Wuruk Perbanas, 2013)
Earnings and cash flow are the two important factors in the company’s life cycle. The researchobjective of this study is to determine the effect of earnings, overall cash flow, andcomponents of earnings on future cash flows of manufacturing companies listed on the IndonesiaStock Exchange at the every stage of company’s lifecycle cycle. The sample used consistsof 99 manufacturing companies listed on Indonesia Stock Exchange (IDX). Secondarydata on the company’s financial statement was taken from the period 2006 to 2010 and thesewere obtained from ICMD (Indonesia Capital Market Directory) and IDX. A data analysistechnique for testing the research problems is linear regression analysis. The results showearnings, overall cash flow, and cash flow components have significant predictive power forfuture earnings and cash flows.